2010
DOI: 10.1348/014466509x441033
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Supervisory Relationship Questionnaire (SRQ) in UK trainee clinical psychologists

Abstract: The SRQ (six subscales, total of 67 items) is a valid and reliable measure of the SR from the supervisee perspective. The present findings support existing models of the SR, and its distinct nature during training as an educative and evaluative process. The SRQ is a promising tool for further research, and is likely to be useful in supervisor training and clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 28 publications
7
93
0
8
Order By: Relevance
“…Each item is rated on a seven point Likert scale ranging from Strongly Disagree to Strongly Agree, providing a total score (maximum 469). The SRQ has a high reliability and validity (Palomo, Beinart, and Cooper 2010). The authors do not provide an optimum score; however their sample obtained a mean SRQ score of 364 (SD 69.9).…”
Section: : Structured Feedback From Superviseementioning
confidence: 92%
See 1 more Smart Citation
“…Each item is rated on a seven point Likert scale ranging from Strongly Disagree to Strongly Agree, providing a total score (maximum 469). The SRQ has a high reliability and validity (Palomo, Beinart, and Cooper 2010). The authors do not provide an optimum score; however their sample obtained a mean SRQ score of 364 (SD 69.9).…”
Section: : Structured Feedback From Superviseementioning
confidence: 92%
“…Each participant is required to obtain feedback from at least one of their supervisees using the Supervisory Relationship Questionnaire (SRQ) (Palomo, Beinart, and Cooper 2010) and/or the Short Supervisory Relationship Questionnaire (SSRQ) (Cliffe, Beinart, and Cooper 2016) or the Leeds Alliance in Supervision Scale (LASS) (Wainwright 2010). The SRQ consists of six subscales with a total of 67 items.…”
Section: : Structured Feedback From Superviseementioning
confidence: 99%
“…Such analysis can examine the level of perceived organizational support (Eisenberger et al, 1986), psychological safety (Edmondson, 1999) or perceived security of supervisor-subordinate relationship (Palomo, Beinart & Cooper, 2010). The low level of these factors would basically indicate that an official intervention might be perceived as threatening among organizational members.…”
Section: Practical Considerations Of Radical Candor Interventionmentioning
confidence: 99%
“…Use of such measures has been criticised because of the failure to acknowledge differences between the therapeutic and supervisory relationship, such as the focus on the professional development of the supervisee (Palomo et al 2010). …”
Section: 4mentioning
confidence: 99%
“…The questionnaire was developed from the views of supervisees concerning the factors of the supervisory relationship that contributed most and least to their clinical effectiveness (Beinart, 2004, as cited in Palomo et al, 2010). Initial research suggests that 'a safe base' was the most important factor reported by trainee clinical psychologists (Palomo et al, 2010).…”
Section: Palomo Et Al (2010) Used Exploratory Factor Analysis To Devmentioning
confidence: 99%